Financial structure and financial sustainability of Microfinance Institutions in Kenya - Cheboi, Livingstone Talel; Asienga, Irene; Otuya, Robert (Junal Ilmu Manajemen, 2024)
This study investigated the effect of financial structure on microfinance firms’ financial sustainability. The study utilized panel data from 32 Microfinance Institutions (MFIs), resulting in 320 firm-year observations for the period of 2010-2019. The dataset was obtained from MIX market, a global database that collects self-reported information from MFIs. The study used a battery of panel data regression methods to test the hypotheses. The regression analysis indicated a statistically significant negative association between debts and donations and the financial sustainability of MFIs in Kenya. In contrast, there was a positive relationship between deposits and equity and the sustainability of microfinance firms in Kenya. Therefore, MFIs are strongly advised to prioritize internal financing in order to achieve financial sustainability. In addition, it is advisable for MFIs to avoid excessive dependence on donations and commercial funding, as these sources of funds often come with strict requirements and conditions that could impede their progress towards achieving financial stability. The results of this study can offer valuable insights to MFIs managers and regulators in formulating financing strategies that can assist MFIs in achieving financial sustainability.